THE PRODUCTIVE CITIES OF PERU - Cavani Grau, Carlos (2014)
A productive city is a model of socio-economic development based on consortium-productive or clusters composed of chains of linkages productive front and back, with size critical, arranged and organized fully to the sales and export. Exposed - this is the product of a research - based with an extensive bibliography, as well as multiple examples that allow us to assert that the Organization of productive cities is possible in the medium and long term.The local economy of a district demand multiple services, offices and commercial business which almost do not exist today. There are, as a huge need to increase the density of enterprises in the new neighborhoods of Lima. And neighborhood businesses generate employment in the neighborhoods (Infante, 2012). Productive cities are integrated mainly by micro, small and medium-sized enterprises. But, we sustain that Gamarra is a nascent cluster, such as product - inter alia - of the gap between small businesses big business and structural vulnerabilities that arise enterprises in our country, Gladys Triveño comment.